Answer:
Answer:x = 7+4√3
Answer:x = 7+4√3To find √x we proceed,
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3√x = 2+√3
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3√x = 2+√31/√x = 1/(2+√3)
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3√x = 2+√31/√x = 1/(2+√3)Multiplying both numerator and denominator by 2 - √3, we get
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3√x = 2+√31/√x = 1/(2+√3)Multiplying both numerator and denominator by 2 - √3, we get1/√x = (2-√3)/(2-√3)(2+√3) = (2-√3)/(2²-√3²) =
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3√x = 2+√31/√x = 1/(2+√3)Multiplying both numerator and denominator by 2 - √3, we get1/√x = (2-√3)/(2-√3)(2+√3) = (2-√3)/(2²-√3²) =1/√x = 2-√3
Answer:x = 7+4√3To find √x we proceed,√x = √(7+4√3)√x = √(7+2x2√3)√x = √(7+2√3x4)√x = √(3+4+2√3x4)….. {writing 7 = 3+4}If we observe RHS of √x we observe form of√(a² + b² +2ab) where a=√3 and b =√4Hence, √x =√(√3 +√4)² = √3 + √4 = 2+√3√x = 2+√31/√x = 1/(2+√3)Multiplying both numerator and denominator by 2 - √3, we get1/√x = (2-√3)/(2-√3)(2+√3) = (2-√3)/(2²-√3²) =1/√x = 2-√3Hence √x +1/√x = 2+√3 +2 -√3 = 4